MELIBATKAN SISWA EFL SMP DALAM KEGIATAN MEMBACA EKSTENSIF DENGAN BANTUAN NOVEL DIGITAL - Hikmi, Marsa Aghni Nurul; Abas, Totoh Tauhidin; Mobit, Mobit (Peneliti.net, 2023)
Extensive reading has been suggested as one of the most successful ways to develop reading skills. The aim of this researchers is to investigate teachers’ strategy in involving students in extensive reading classes using digital novel media, and to explore the students' views in participating in. The data collection was carried out through observation and interviews. An English teacher and six students of class IX participated in this study. This researchers aimed to investigate the application of teachers involving students in extensive reading classes using digital novel media, and to explore the students' views in participating in extensive reading learning assisted by digital novels. This study uses qualitative researchers that focuses on students' experiences in reading extensively with the help of digital novels in making reviews. In addition, the researchers uses a narrative inquiry method to explore students' experiences of extensive reading with the help of digital novels. Researchers also use interviews to collect data and a list of questions as researchers instrumentation. The results show that the use of the digital novel in involving students in extensive reading classes makes students very active and enthusiastic in the extensive reading activities. the students enjoyed reading activities . In addition, students were interested in learning to read extensively because they felt that extensive reading activities assisted by digital novels make them accustomed to reading unconsciously. However, there are several challenges faced by the students such as difficulties in technical problems, some students also faced with poor signal connections problems. Furthermore, the students found that the use of the digital novels was more economical, practical, and accessible and attractive in design. Thus, students thought that the extensive reading technique mediated by digital novels is suitable for learning to read.